Deconstructing Religious Patriarchy in the Bidaah Series: An Analysis through Asghar Ali Engineer's Hermeneutics of Liberation - Makkis Fuadatal Qodisiyah; Mohammad Yahya; Syahril Siddik (AJIS: Academic Journal of Islamic Studies, 2026)
This research investigates the construction of patriarchal values embedded in the religious discourse portrayed in the Malaysian television series *Bidaah* by employing Asghar Ali Engineer's hermeneutics of liberation as its analytical framework. Using a qualitative interpretive methodology, the study examines audiovisual narratives through the interconnected dimensions of text, context, and perspective to uncover the ways religious representations produce and legitimize patriarchal forms of authority. The analysis indicates that the series reinforces patriarchal ideology by depicting male characters as the primary holders of religious legitimacy, moral authority, and social dominance, while simultaneously normalizing gender inequality through charismatic leadership, polygamous practices, and hierarchical family relationships. Viewed from the perspective of Engineer's hermeneutics of liberation, these portrayals reflect socio-cultural constructions rather than authentic Islamic teachings, as they are inconsistent with the fundamental Islamic principles of justice, equality, and respect for human dignity. The findings offer valuable insights for educators, media professionals, and researchers in critically assessing religious narratives in audiovisual media and in fostering gender-responsive religious literacy based on egalitarian Islamic principles. By applying Engineer's hermeneutics of liberation to the study of a contemporary Islamic television drama, this research contributes to the existing literature by illustrating how popular media serve as an important arena for challenging religious authority, reshaping gender relations, and encouraging the development of progressive Islamic discourse.